Nutrients and Heavy Metal Removal From Landfill Leachate by Sub-Surface Flow (SSF) Constructed Wetlands Planted With Limnocharis Flava and Scirpus Atrovirens - Nor Shazwani Ismail (Penerbit Universiti Malaysia Perlis, 2011)
Landfill leachate classified as problematic wastewaters and represents a dangerous source of pollution for the environment due to its fertilizing and toxic effects. Thus, leachate must be treated at the leachate treatment plant before being discharged into the waterways or lakes. Failure to treat the effluent from the landfill caused the content of organic and inorganic materials which absorb the unwanted entry into the ground next to waterways and lakes. There are various options to treat landfill leachate and constructed wetland is one of efficient method to treat this landfill leachate. This study focus on the efficiency of horizontal sub-surface flow (SSF) constructed wetland in the removal of nutrients and heavy metals in landfill leachate. Where, it is also to compare the efficiency of two species which is Limnocharis flava and Scirpus atrovirens in removing nutrients and heavy metals in leachate. This is done by measuring the amount of heavy metals accumulated and retained in the plants root and aerial part (stem and leaves) and also in the soil media.